2019
DOI: 10.1590/0001-3765201920180699
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan inhibits inflammation through an angiotensin II type 1 receptor independent way in human embryonic kidney epithelial cells

Abstract: Besides stimulating vasoconstriction, Angiotensin II is also well known in inducing reactive oxygen species and promoting inflammatory phenotype switch via its type 1 receptor. In clinic, Angiotensin II type 1 (AT1) receptor blocker like candesartan has been widely applied as an antihypertensive medication. We previous have demonstrated that a higher dose of candesartan plays a protective role after kidney injury. However, whether candesartan could exhibit anti-inflammatory effects remains unclear. Here, by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…However, there was no difference in the normotensive and hypertensive animals' responses, suggesting that its signaling was not related to the bone fragility differences between the Wistar and SHRs. Yu et al (2019) demonstrated the in vitro anti-inflammatory effect of candesartan in human embryonic kidney epithelial cells (HEK lineage), possibly associated with reduced oxidative stress, independent of the At1r receptor. The present study's results suggest that other mechanisms could have been involved in the protective effect of TELM on the bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in the normotensive and hypertensive animals' responses, suggesting that its signaling was not related to the bone fragility differences between the Wistar and SHRs. Yu et al (2019) demonstrated the in vitro anti-inflammatory effect of candesartan in human embryonic kidney epithelial cells (HEK lineage), possibly associated with reduced oxidative stress, independent of the At1r receptor. The present study's results suggest that other mechanisms could have been involved in the protective effect of TELM on the bone.…”
Section: Discussionmentioning
confidence: 99%
“…CS has been demonstrated to exert anti-inflammatory activities in vitro and in vivo . CS significantly reduced the expression levels of IL-6 and transforming growth factor-β (TGF-β) in TNF-α-stimulated human embryonic kidney epithelial cells ( 41 ). CS decreased the expression of Th1 and Th2 cytokines in the lung tissues of mice with ovalbumin-induced allergic asthma ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, candesartan inhibits inflammation by modulating signaling cascades dependent on TNF-α, IL-1beta, IL-2, IL-6, TGF-β, and NF-κB. In addition, it reduces the formation of ROIs by phagocytes and lowers the expression of CD25 and IL-2 release by T cells [113,[124][125][126][127][128][129]. However, this medicament seems to not affect the secretion of IL-10 [130], similarly to olmesartan [121].…”
Section: Candesartan Irbesartanmentioning
confidence: 99%
“…-IL-1beta [31], IL-6 and IL-8 concentration [31,32,85]; -CRP concentration [41]; -TNF-alfa concentration [41,113,[124][125][126][127][128][129]; -lymphocyte proliferation and IFN-gamma production in vitro assays, and suppressed antigen-specific Th1 and Th2 lymphocytes in vivo [115]; -formation of ROIs by phagocytes [113,[124][125][126][127][128][129]; -the expression of CD25 and IL-2 release by T cells [113,[124][125][126][127][128][129]; -the general number of immune cells in bronchoalveolar lavage fluid [125]; -the release of Th2-lymphocyte (IL-4, IL-5 and IL-13) and Th1-lymphocyte (IL-2 and IFN-γ) cytokines [125].…”
Section: Reduction Inmentioning
confidence: 99%